2015
DOI: 10.11606/rai.v12i1.100320
|View full text |Cite
|
Sign up to set email alerts
|

O Impacto Da Cultura Sobre Ambiente Propício Ao Desenvolvimento De Inovações

Abstract: O objetivo geral deste estudo é analisar o impacto da cultura organizacional sobre o ambiente propício ao desenvolvimento de inovações em uma empresa do setor metal-mecânico. Para tanto foi realizada uma pesquisa quantitativa descritiva, transversal. A amostra compôs 156 respondentes, e os dados foram analisados por meio de modelagem de equação estrutural. Como principal resultado, os empregados da empresa estudada destacaram as dimensões Resultados, Processos, Recursos, Liderança, Relacionamento Interno ao Gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 51 publications
1
4
0
Order By: Relevance
“…The research has shown, according the results, that an organization with a Clan culture positively impacts the perception of the environment of development of innovations. The results of the present study corroborate the hypothesis of previous studies by Machado (2004), Machado et al (2012), Machado & Carvalho (2013), Scarpin (2012), Depiné & Machado (2015), Neumann (2013) and Torres (2014) related to the impact of organizational culture and own environments to the development of innovations.…”
Section: Findings and Limitationssupporting
confidence: 92%
See 3 more Smart Citations
“…The research has shown, according the results, that an organization with a Clan culture positively impacts the perception of the environment of development of innovations. The results of the present study corroborate the hypothesis of previous studies by Machado (2004), Machado et al (2012), Machado & Carvalho (2013), Scarpin (2012), Depiné & Machado (2015), Neumann (2013) and Torres (2014) related to the impact of organizational culture and own environments to the development of innovations.…”
Section: Findings and Limitationssupporting
confidence: 92%
“…In continuity, the frequencies of the means of the phases and the dimensions, before and after the reduction of the data, were compared by means of the Chi-square test. Churchill Junior (1979) and Stratman & Roth (2002) argue that this methodology validates the reduction of data in the evaluation of constructs (Scarpin, 2012).…”
Section: D7mentioning
confidence: 89%
See 2 more Smart Citations
“…However, the research on the topic is still incipient for emerging markets. Some authors get deeper into the subject, as Gasparindo (2014); Scarpin and Machado (2012); Machado and Vasconcelos (2007), but their studies are restricted to a sector or a country.…”
Section: Introductionmentioning
confidence: 99%